A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae) - Lee, Seung-Gyu; Ahn, Kee-Jeong (Zootaxa, 2017)
A taxonomic review of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson in Korea is presented. A new synonym is proposed: Datomicra Mulsant & Rey, 1874 = Datostiba Sawada, 1976, syn. nov. The subgenus is represented in Korea by eight species including a new species, Atheta (Datomicra) semidentiventris Lee & Ahn, sp. nov. Two species [A. (D.) dadopora Thomson and A. (D.) dentiventris Bernhauer] are new to the Korean Peninsula and one [A. (D.) celata (Erichson)] to South Korea. A key, descriptions, habitus photographs and illustrations of the diagnostic characters of the new species and two newly recorded species are provided.